Worked-Example Method on Mathematical Problem-Solving Ability in term of Students’ Initial Ability - Santosa, Cecep Anwar Hadi Firdos; Rafianti, Isna; Yulistiany, Dita (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2022)
The reserch aims to understanding the phenomena of differences in mathematical problem-solving ability between students who obtained worked-example and expository learning method when reviewed from students’ initial ability. This study was a quasi-experimental with treatment by level 2×2 research design. We analize the data used two-way analysis of variance. We found that (1) There were differences in mathematical problem-solving ability between students who obtained worked-example and expository learning method. (2) There were differences in mathematical problem-solving ability between students who had high and low initial ability. (3) In high initial ability, students who obtained expository and worked-example learning method were relatively the same. (4) In low initial ability, students who obtained worked-example learning method were better than expository. (5) There was an interaction between learning method and initial ability in mathematical problem-solving ability.Penelitian yang dilakukan ingin memahami fenomena perbedaan kemampuan pemecahan masalah matematis antara siswa yang memperoleh metode pembelajaran worked-example dan ekspositori ditinjau dari kemampuan awal siswa. Penelitian ini merupakan penelitian kuasi eksperimen dengan desain treatment by level 2×2. Penlitian ini menggunana analisis variansi dua jalan untuk menganalisis data penelitian. Dalam penelitian ini ditemukan bahwa (1) Ada kemampuan yang berbeda pada pemecahan masalah matematis antara siswa yang memperoleh metode pembelajaran worked-example dan ekspositori; (2) Ada perbedaan pada kemampuan pemecahan masalah matematis antara siswa yang memiliki kemampuan awal tinggi dan rendah; (3) Pada siswa dengan kemampuan awal tinggi, relatif tidak ada perbedaan pada kemampuan pemecahan masalah matematisnya; baik siswa yang memperoleh metode pembelajaran ekspositori dan worked-example; (4) Pada kemampuan dengan awal rendah, ada perbedaan dan siswa dengan metode pembelajaran worked-example lebih baik dibandingkan siswa yang belajar dengan ekspositori, dilihat dari kemampuan pemecahan masalah matematis; (5) Terdapat interaksi antara metode pembelajaran dan kemampuan awal terhadap kemampuan pemecahan masalah matematis.